Supramolecular ordering of difuryldiketopyrrolopyrrole: the effect of alkyl chains and inter-ring twisting. Issue 23 (6th April 2016) - Fu, Chaoying; Bélanger-Gariépy, Francine; Perepichka, Dmitrii F.
Abstract : Combined XRD, STM and DFT studies reveal the details of supramolecular ordering of difuryldiketopyrrolopyrrole in monolayers and 3D crystals. Abstract : We report the first study of supramolecular ordering of difuryldiketopyrrolopyrrole (DFDPP), an important building block for semiconducting materials, in 3D crystals and 2D monolayer films. Combined X-ray diffraction (XRD), scanning tunnelling microscopy (STM) and density functional theory (DFT) calculations underline the mutual roles of alkyl chains and pending aryl substituents in molecular planarity and packing.